Update on the management of poor ovarian response in IVF: the shift from Bologna criteria to the Poseidon concept - Drakopoulos, Panagiotis (Ther Adv Reprod Health, 2020)
Despite the considerate progress to which assisted reproduction technology (ART) has been subject since 1978, some issues remain unresolved. Notably, the clinical management of patients with a poor ovarian response is still a challenge in everyday practice, frustrating to both the patient and the fertility expert. Poor ovarian responders (PORs) embody 9–24% of patients undergoing ovarian stimulation, meaning that up to one in four patients conceals a poor reproductive prognosis. The last decade has witnessed the attempts of the medical community to standardize diagnosis of POR with the developing of the Bologna Criteria and the subsequent evolution of the low prognosis patient elaborated in the POSEIDON classification. The aim of this article is to summarize all evidence concerning etiology and management of poor ovarian response, including the most recent advances and future prospects in this regard.